Bellomo, Manlio, The Common Legal Past of Europe, Washington D. C. 1995 (= Studies in Medieval and Early Modern Canon Law; 4) [Rezension] - Brundage, James A. 1929-2021 (1996)
Aufnahme: BO Z 851
Keywords: Recht; Geschichte; Mittelalter; Europa; Rezension